Fragile X–Related Protein 1 Regulates Nucleoporin Localization in a Cell Cycle–Dependent Manner - Agote-Arán, Arantxa; Lin, Junyan; Sumara, Izabela (Frontiers in Cell and Developmental Biology, 2021)
Nuclear Pore Complexes (NPCs) are embedded in the nuclear envelope (NE) where they ensure the transport of macromolecules between the nucleus and the cytoplasm. NPCs are built from nucleoporins (Nups) through a sequential assembly order taking place at two different stages during the cell cycle of mammalian cells, at the end of mitosis and during interphase. In addition, Fragile X-related proteins (FXRPs) can interact with several cytoplasmic Nups and facilitate their localization to the NE during interphase through a microtubule-dependent mechanism. In the absence of FXRPs or microtubule-based transport, Nups aberrantly localize to the cytoplasm forming the so called cytoplasmic nucleoporin granules (CNGs), compromising NPCs’ function on protein export. However, it remains unknown if Nups synthesis or degradation mechanisms are linked to the FXRPs-Nup pathway and if and how the action of FXRPs on Nups is coordinated with the cell cycle progression. Here we show that Nups localization defects observed in the absence of FXR1 are independent of active protein translation. CNGs are also cleared in an autophagy- and proteasome-independent manner and their presence is restricted to early G1 phase of the cell cycle. Our results thus suggest that a pool of cytoplasmic Nups exists that contributes to the NPC assembly specifically during early G1 to ensure NPC homeostasis at a short transition from mitosis to the onset of interphase.